Ensinando conceitos de matemática a partir de jogos online na 7ª serie do ensino fundamental : desafios e oportunidades - Rubi, Geiseane Lacerda (2012)
Mathematics is generally considered a complex subject by students. It causes a feeling known as Matofobia (Math fear). An option to help to reduce Matofobia is to diversify the way the subjects relate to Math is taught. In this sense, the use of games as a resource to learn can help young people to overcome their resistance and/or fear to learn mathematics concepts, considering game playing nowadays is part of the student‟s daily life. The use of online commercial games as elements to support Math teaching can help students to learn in a more enjoyable and interesting way. Playing games allow students to acquire skills and abilities in order to help them to establish important relationships regarding Math concepts. In this sense, this master dissertation presents a methodological proposal based on the online game named Transformice as a tool to teach Math concepts. A sequence of didactic steps related to Space and Form and Quantities and Measurements was tested in order to prove the methodology potential. Concepts and relationships among angles, arcs, Pythagorean Theorem, were tested with students from elementary school (7th grade). This research used a qualitative approach organized as a case study. In order to collect data we have used questionnaires, interviews, and daily classroom logs. To analyze these data we performed Moraes and Galiazzi Textual Discursive Analysis. The results showed us that expectations related to the use of a commercial game online properly contextualized by a pedagogical helps students to study math concepts causing a double beneficial effect: understanding the application of the studied content to solve everyday problems, and it also helps them to improve their skills as players.